2017
DOI: 10.5489/cuaj.4370
|View full text |Cite
|
Sign up to set email alerts
|

Never events and hospital-acquired conditions after kidney transplant

Abstract: Introduction: Never events (NE) and hospital-acquired conditions (HAC) after surgery have been designated as quality metrics in healthcare by the centres for Medicare and Medicaid Services (CMS). Methods: The Nationwide Inpatient Sample (NIS) database 2002-2012 was used to identify patients underwent kidney transplant. Multivariate analysis using logistic regression was used to identify outcomes and risk factors of HAC and NE after transplantation; however, we were limited by using a retrospective database mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
7
0
4
Order By: Relevance
“…Several studies have reported the importance of patient factors to the development of HAC. [7][8][9][10][11][12][13] Wen et al8 studied the influence of patient factors on NE and HAC occurrence following cerebrovascular surgery; they noted that age and the presence of ≥ 2 comorbidities were strong independent predictors of HACs. They also advocated for development of risk-adjusted models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the importance of patient factors to the development of HAC. [7][8][9][10][11][12][13] Wen et al8 studied the influence of patient factors on NE and HAC occurrence following cerebrovascular surgery; they noted that age and the presence of ≥ 2 comorbidities were strong independent predictors of HACs. They also advocated for development of risk-adjusted models.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with other reports regarding the association between NE and HAC with patient outcomes, increased hospital charges, and length of hospital stay. [7][8][9][10][11] With this administrative data, however, we cannot determine whether HACs represent a causative factor on morbidity, mortality, and hospital charges; the data can only identify a correlation. And, since HAC most strongly correlated with high patient comorbidity, present preoperatively, it is possible that patient morbidity is the primary factor driving morbidity, mortality, hospital charges, and HAC development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAUTI disproportionately affect solid organ transplant (SOT) recipients, with the most data available for kidney transplant recipients. In an analysis of kidney transplant recipients in the United States from 2002 to 2012, 7.5% of kidney transplant recipients developed CAUTI [29]. Patient-specific risk factors for CAUTI in kidney transplant include age, female sex, and pre-transplant loss of function.…”
Section: Catheter-associated Urinary Tract Infectionsmentioning
confidence: 99%
“…Por último, otro de los factores que predispone para el desarrollo de ITU en el receptor de un TR es la presencia de Diabetes Mellitus 10,11,21 . Otra de las causas de infección presente en los receptores de un TR es, según la bibliografía 22 , la infección relacionada con catéter. Esto se debe al uso de catéteres venosos centrales (CVC) como práctica habitual, ya que está especialmente indicado en aquellos pacientes que precisan de un acceso venoso por tiempo prolongado, ya sea para la administración de medicación o para la extracción de sangre.…”
Section: Introductionunclassified